Bathymetric fluctuations as an effect of breaking wave action based: example of a selected section of the Baltic Sea coastal zone - Choiński, Adam (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
Transformations of the bottom of a section of the coastal zone of the Baltic Sea were determined based on its corings. The measurements were performed before and after a storm. The method of determining the transformations involved combining bathymetric plans. This way, deepening and shallowing areas of the bottom were identified. The changes result from the return of currents on the bottom and from a lower degree of the littoral current and direct effect of the waves.
Keywords: bathymetric fluctuations; return currents; Baltic Sea